Comparison of bias resulting from two methods of self-reporting height and weight: a validation study. (6th May 2014) - Scribani, Melissa; Shelton, Jessica; Chapel, David; Krupa, Nicole; Wyckoff, Lynae; Jenkins, Paul
Objectives: To contrast the validity of two modes of self-reported height and weight data. Design: Subjects' self-reported height and weight by mailed survey without expectation of subsequent measurement. Subjects were later offered a physical exam, where they self-reported their height and weight again, just prior to measurement. Regression equations to predict actual from self-reported body mass index (BMI) were fitted for both sets of self-reported values. Residual analyses assessed bias resulting from application of each regression equation to the alternative mode of self-report. Analyses were stratified by gender. Setting: Upstate New York. Participants: Subjects ( n  = 260) with survey, pre-exam and measured BMI. Main outcome measures: Prevalence of obesity based on two modes of self-report and also measured values. Bias resulting from misapplication of correction equations. Results: Accurate prediction of measured BMI was possible for both self-report modes for men ( R 2  = 0.89 survey, 0.85 pre-exam) and women ( R 2  = 0.92 survey, 0.97 pre-exam). Underreporting of BMI was greater for survey than pre-exam but only significantly so in women. Obesity prevalence was significantly underestimated by 10.9% ( p  < 0.001) and 14.9% ( p  < 0.001) for men and 5.4% ( p  = 0.007) and 11.2% ( p  < 0.001) for women, for pre-exam and survey, respectively. Residual analyses showed that significant bias results when a regression model derived from one mode of self-report is used to correct BMI values estimated from the alternative mode. Conclusions: Both modes significantly underestimated obesity prevalence. Underestimation of actual BMI is greater for survey than pre-exam self-report for both genders, indicating that equations adjusting for self-report bias must be matched to the self-report mode.